ANALISIS STRATEGI APARATUR DINAS LINGKUNGAN HIDUP DAN PERTANAHAN DALAM PENGELOLAAN SAMPAH DI KABUPATEN TAKALAR - Hendrawati Hamid (JURNAL LENTERA BISNIS, 2024)
This research aims to find out and analyze the strategies implemented by the Environment and Land Service apparatus in managing waste in Takalar Regency. The waste problem in various regions in Indonesia is a very urgent matter that needs attention from officials in each regional government because it is closely related to public health and healthy environmental conditions. This research uses a qualitative descriptive approach method, and the data is analyzed using the SWOT technique. Data collection was carried out by combining observation techniques, in-depth interviews with informants (Heads of Departments, Heads of Divisions, implementing officers in the field, and the general public), as well as documentation data. The findings obtained in this research are that the strategies implemented by the Environment and Land Service apparatus have been working well, although they still require various improvements and attention from the relevant apparatus. This strategy, which has not yet been effective, should receive more serious attention in the waste management process because it has the potential to create new jobs, as well as contribute more to increasing the Gross Regional Domestic Product (GRDP) of Takalar Regency. To improve waste management in Takalar Regency, increase the number of PDUs, TPS3R, and community-based waste banks as well as carry out outreach and create the "SALINTAK" application. Keywords: Strategy Management, Waste Management, SWOT Analysis